Epidendrum edquenii (Laeliinae), a new species from a montane wet forest of the Private Conservation Area La Pampa Del Burro, Amazonas, Peru - Arista, Jessy P.; Hágsater, Eric; Santiago, Elizabeth; Pariente, Eli; Oliva, Manuel; Salazar, Gerardo A. (Lankesteriana: International Journal on Orchidology, 2023)
A new species Epidendrum edquenii, is described and illustrated from the Private Conservation Area La Pampa del Burro, department of Amazonas, northeastern Peru. It belongs to the informal Takulumena group, characterized by Vanda-like monopodial stems with basal or lateral, successive inflorescences. The new species is distinguished by its non-pubescent, red flowers with green dorsal surface, margins, and apices of the sepals and petals, yellow-green base of column and disc of lip, acuminate sepals 9.5–10.7 mm long, narrowly ovate petals with the margin densely and shortly ciliate, and widely triangular lip, 6.0 × 9.5 mm, with the margin scarcely papillose. A list and an identification key for the previously known species of the Takulumena group are provided. Furthermore, the new name Epidendrum vulcanitungurahuae is proposed to replace the illegitimate combination Epidendrum tungurahuae, predated by E. tunguraguae.